Osteological evidence of metabolic diseases from a post medieval North Italy archaeological site. (17th August 2020) - Larentis, Omar; Tonina, Enrica; Iorio, Silvia; Gorini, Ilaria; Licata, Marta
Abstract: Skeletal lesions related to metabolic diseases in children have been systematically investigated in paleopathological literature only in recent years. This work presents an infant pathological specimen from the post-medieval cemetery of the St. Mary's Nativity church (15th–18th centuries, Segno, Trento, Trentino, Northeast Italy). The bones belonged to an individual of 9 ± 3 months of age, estimated upon an assessment of the stage of dental eruption. Metabolic diseases were diagnosed with paleopathological criteria according to previous literature. Differential diagnosis of the osteological evidence indicates a disease that might be caused by the lack of vitamin D or C. Comorbidity of vitamin C and D deficiency has been widely studied in clinical literature, particularly in children between 3 months and 5 years of age. The study of ancient osteoarchaeological materials allows us to improve our knowledge on diseases' effects on bone development in children and, in this case, it represents additional evidence of the presence of metabolic diseases in a rural contest of the Italian post-medieval period.